Moderate electric fields as a potential tool for sustainable recovery of phenolic compounds from Pinus pinaster bark - Santos, Pedro Miguel Ferreira (2019)
Pinus pinaster (pine) bark is a widely available wood industry byproduct but an underexploited source of phenolic compounds with a strong antioxidant activity. The aim of this study was to evaluate the effectiveness of ohmic heating (OH, a recognized eco-friendly, electric fields-based processing technology) for the sustainable recovery of phenolic compounds from Pinus pinaster bark. Results of OH evidenced increased extraction of antioxidant phenolic compounds with no degradation of pine bark extracts for all tested conditions. Moreover, the enhancement in phenolic content in OH-assisted extraction was particularly evident when using a hydroethanolic solvent with 50% ethanol, reaching improvements higher than 100%, when comparing to the conventional approach. This fact may indicate preferential extraction, presumably due to the action of electric field effects acting in synergy with heat and solvents. Furthermore, additional changes in the morphological structure of bark cells were observed upon OH-assisted extraction, suggesting membrane electroporation effects. A significant reduction in energy consumption when compared with the conventional process was observed, leading to an energetically more sustainable approach. OH technology holds the potential to be a “green” alternative, with higher extraction yields and reduced energy consumption and offering the possibility of tuning the selectivity toward phenolic compounds.